ASSESSMENT OF THE IMPACTS OF INDUSTRIAL EFFLUENT DISCHARGES ON THE EPILITHIC DIATOMS COMMUNITY AND WATER QUALITY OF SAHNAHAN STREAM, MALATYA, TURKEY - Celik, Betul; Yildirim, Vesile (Parlar Scientific Publications (P S P), 2017)
In this study, the effect of an industrial effluent discharges on the water quality and epilithic algae of Sahnahan Stream (Malatya-Turkey). Sahnahan stream's epilithic algae and water quality were examined between May 2012-April 2013 which identified 3 station taken the samples of monthly periods. During the study, a total of 141 taxa were identified, most of which belonged Bacillariophyta (123), other taxonomic groups present were Chlorophyta (9), Cyanophyta (5), Charophyta (3) and Dinophyta (1). Temperature, pH, total hardness dissolved oxygen, organic matter, nitrit, nitrat sulfate, total phosphore, orthophosphate were measured and analysed. Water quality and epilithic algal community differed significantly between sites upstream and downstream of the discharge. At the same time, changes in the dominant algae groups were observed.
Keywords: Water quality; Stream; Epilithic algae; Pollution; Biothic indices